Carbon Nanotubes: Printed Carbon Nanotube Electronics and Sensor Systems (Adv. Mater. 22/2016). Issue 22 (6th June 2016) - Chen, Kevin; Gao, Wei; Emaminejad, Sam; Kiriya, Daisuke; Ota, Hiroki; Nyein, Hnin Yin Yin; Takei, Kuniharu; Javey, Ali
Abstract : Printed electronics and sensors enable new applications ranging from low‐cost disposable analytical devices to large‐area sensor networks. Recent progress in printed carbon nanotube electronics in terms of materials, processing, devices, and applications is discussed on page 4397 by A. Javey and co‐workers. The research challenges and opportunities regarding the processing and system‐level integration are also discussed for enabling of practical applications.